The Spatial Spillover of Health on Regional Economies: A Spatial Durbin Model Analysis - Rinusara, Novita Mukti (Economics, Business, Accounting & Society Review, 2025)
The purpose of this study is to examine the direct and spillover effects of population health on regional economic performance at the sub-national level in a developing country context. Using regency- and city-level data from Central Java Province, Indonesia, the study employs a Spatial Durbin Model (SDM) to capture both direct impacts within a region and indirect spillover effects across neighboring regions. The model integrates health indicators—such as life expectancy and morbidity rates—with regional economic performance measures, while controlling for socioeconomic and demographic covariates. This spatial econometric approach ensures that interdependencies across administrative boundaries are properly addressed, offering a more comprehensive assessment compared to traditional regression models. The results reveal that improvements in regional health conditions significantly enhance local economic growth, while also producing positive spillover effects in adjacent regions. Specifically, better health outcomes increase labor productivity and expand economic capacity beyond local boundaries, suggesting that regional health is not only a localized asset but also a shared driver of development. Moreover, the findings highlight that neglecting health disparities among neighboring regions can diminish aggregate economic performance, underlining the importance of coordinated health interventions. The study contributes to the literature by providing empirical evidence from a developing country at the sub-national level, a setting often overlooked in prior research dominated by cross-country or national analyses. The findings carry practical implications for policymakers, emphasizing that investments in regional health systems not only foster local prosperity but also strengthen broader regional economic resilience.